Sistem Informasi Point Of Sale (Pos) Pada Rumah Makan Berkah Illahi - Arif Kurniawan; Nonot Wisnu Karyanto (Melek IT : Information Technology Journal, 2017)
Lack of knowledge about POS (point of sale) on the information system is needed for RM. God's Blessing. In this case, can trigger the development of technology. Because at this time the system used is still the manual system. The purpose of this study is to create an application that can help recording transactions by order and payment. The research method used is waterfall method include data analysis in the form of collecting Data needed sourced from book literature study and journal and do an interview with a restaurant owner, then design, coding, and testing system. This study aims to conduct transactions based on existing reservations in the blessing house divine.Keywords: Point of sale, POS, restaurant.